Sergeant on stamp duties : Supplement to sixth edition, including capital duty - Sims, Bernard John; England; Tavare, A. K. (London : Butterworths, 1973)
This is a full description of capital duty of the European Economic Community (EEC).
asm 23/01/2019
Loans
Keywords: Stamp duties; Stamp taxes; Great Britain